Peran Komitmen Organisasional sebagai Variabel Mediasi pada Pengaruh Budaya Organisasi terhadap Organizational Citizenship Behavior - Serpian Serpian (University of Merdeka Malang, 2021)
This research aimed to examine the indirect effect of organizational culture on organizational citizenship behavior (OCB) through organizational commitment as the mediating variable. Formulation of the problem in this research attempted to know about what organizational commitment that can mediate the effect of organizational culture on OCB. The path analysis was used to examine 80 respondents. The sample collection was retrieved by asking employees from each main branch banks to spread out the questionnaires. Researcher deployed 103 questionnaires yet only 86 questionnaires was returned and 80 questionnaires could be examined. These variables had been previously verified in BNI life Regional Makassar. This research concerns on the problems of the high rate of employee turnover in BNI life regional Makassar. Every year, many employees decide to resign from the bank. Besides, this research was based on the research gap, the different results of research by Giri, Nimran, Hamid, Musadieq (2016), and Meijen (2007). A study by Giri, Nimran, Hamid, Musadieq (2016) showed that there are the significant impacts of organizational culture on organizational commitment. In contrast, the result of research by Meijen (2007) revealed that there was no impact on the variables. The result of this research found that there is an indirect impact between organizational cultures on organizational citizenship behavior (OCB) through organizational commitment as the mediating variable. The conclusion is the strategic decision making related to human resource development must consider organizational culture.